The results of the analysis of "willingness –to–pay" for the use of innovative technologies in the treatment of patients with depressive disorders - Khaliq, R. N.; Yakovleva, O. S.; Яковлева, Ольга Станіславівна (Х.: НФаУ, 2016)
Introduction. Currently, the organization of effective medical and pharmaceutical care of patients suffering from depressive disorder in Ukraine is of great socio-economic importance. The introduction of modern multimodal antidepressants into the treatment of patients with depressive disorders allows using them for a long time to achieve full recovery and supports the premorbidal level of social functioning. Innovative drug Vortioxytine corresponds to the important contemporary requirements which are put forward for the treatment of depression, has not only a high efficiency in relation to affective symptoms, but also unique properties to enhance cognitive functioning and, consequently, the quality of life of the patient. However, the application of new approaches is complicated by the problem of its high cost. Aim. To make the analyzes of "willingness-to-pay" in the organization of treatment of patients with depressive disorders in Ukraine.